Sistemas de contraventamento aplicados em estruturas pré-moldadas de concreto de múltiplos pavimentos - Santos, Luciano Ferreira (2015)
The use of precast concrete system in multi-storey buildings demand for structural solutions that enable its horizontal stability without implicating the architectural and economic aspects, its challenge is borne by the structural engineer, who often need to assign additional structures (substructures of bracing) that provide the rigidity necessary to ensure the overall stability of the assembly. This study aims to analyze and evaluate the technical and economic performance of bracing systems applied to buildings with multiple floors with precast concrete structure and can be justified by the current need to develop appropriate technically ways of choice in the constructive system. The development of this study is the analysis of global stability in multi-storey buildings with the application of bracing systems, evaluating the influence of the stiffness and the arrangement of these elements in the performance of the structure, and comparing the concrete consumption values of the structures formed by beams and columns (disregarding the slabs and the foundation), and also values of the efforts in the foundation. To develop this study we used the commercial software STRAP® as a support tool for calculations, where the results gotten by it, showed that the bracing substructures improved the behavior of the structures analyzed in the issue of global stability. Finally, they were provided the necessary subsidies for the proper choice of the wind bracing system to be employed on the structures analyzed in this work.